Legal issues and underexplored data protection in medical 3D printing: A scoping review - Pettersson, Ante B. V.; Ballardini, Rosa Maria; Mimler, Marc; Li, Phoebe; Salmi, Mika; Minssen, Timo; Gibson, Ian; Mäkitie, Antti (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: 3D printing has quickly found many applications in medicine. However, as with any new technology the regulatory landscape is struggling to stay abreast. Unclear legislation or lack of legislation has been suggested as being one hindrance for wide-scale adoption. Methods: A scoping review was performed in PubMed, Web of Science, SCOPUS and Westlaw International to identify articles dealing with legal issues in medical 3D printing. Results: Thirty-four articles fulfilling inclusion criteria were identified in medical/technical databases and fifteen in the legal database. The majority of articles dealt with the USA, while the EU was also prominently represented. Some common unresolved legal issues were identified, among them terminological confusion between custom-made and patient-matched devices, lack of specific legislation for patient-matched products, and the undefined legal role of CAD files both from a liability and from an intellectual property standpoint. Data protection was mentioned only in two papers and seems an underexplored topic. Conclusions: In this scoping review, several relevant articles and several common unresolved legal issues were identified including a need for terminological uniformity in medical 3D printing. The results of this work are planned to inform our own deeper legal analysis of these issues in the future.